2011
DOI: 10.1136/bmj.d223
|View full text |Cite
|
Sign up to set email alerts
|

Emotional distress in infertile women and failure of assisted reproductive technologies: meta-analysis of prospective psychosocial studies

Abstract: Objective To examine whether pretreatment emotional distress in women is associated with achievement of pregnancy after a cycle of assisted reproductive technology. Design Meta-analysis of prospective psychosocial studies. Data sources PubMed, Medline, Embase, PsycINFO, PsychNET, ISI Web of Knowledge, and ISI Web of Science were searched for articles published from 1985 to March 2010 (inclusive). We also undertook a hand search of reference lists and contacted 29 authors. Eligible studies were prospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
200
2
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(237 citation statements)
references
References 43 publications
8
200
2
14
Order By: Relevance
“…Fertility treatment for our participants was associated with a range of negative emotions, which is consistent with earlier literature [6] [23] [30] [31] [32]. In addition our participants described positive emotions that could occur, especially hope.…”
Section: Comparison With the Existing Literaturesupporting
confidence: 81%
See 1 more Smart Citation
“…Fertility treatment for our participants was associated with a range of negative emotions, which is consistent with earlier literature [6] [23] [30] [31] [32]. In addition our participants described positive emotions that could occur, especially hope.…”
Section: Comparison With the Existing Literaturesupporting
confidence: 81%
“…One woman from our study consulted a medical psychologist and found this very helpful. Boivin, et al [30] and Péloquin [8] confirmed that talks with a psychologist help to reduce stress. The role of peer-support through internet forums is fairly new to the literature and can reflect the emerging role of internet in health-related behaviours.…”
Section: Comparison With the Existing Literaturementioning
confidence: 86%
“…From the beginning, clinicians should clarify to couples the fact that elevated negative emotions in women are natural under the circumstances and will not affect the pregnancy rate [42]. The couples should also be provided with information and support, which will give them a better understanding of the process, more realistic expectations about the outcome of the treatment, and the strength to go through the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The role that stress may exert on reproductive functioning has remained a topic of debate for decades (Boivin and Venetis., 2011;Mathiesen et al, 2011). This debate has been fuelled not least by the complexities of delineating plausible psychobiological pathways by which stress might influence reproductive outcomes (Whirledge and Cidlowski, 2010;Toufexis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%